Active Switching of Toroidal Resonances by Using a Dirac Semimetal for Terahertz Communication - Sun, Yuanbao; Liao, Denggao; Xu, Jinjin; Wu, Yiping; Chen, Lin (Frontiers in Physics, 2020)
Toroidal dipole is a nonradiating electromagnetic excitation and manifest as poloidal surface currents on the split ring resonators. In this paper, the dynamical switching of the toroidal dipole resonance channel is demonstrated, through the Fermi level selection of Dirac semimetal on back substrate. As the Fermi level of Dirac semimetal increased from 30 meV to 150 meV, the resonance frequency is switched from 0.283 THz to 0.201 THz due to the transition from toroidal mode to hybrid mode formed by the interaction between toroidal mode and plasmonic mode induced by Dirac semimetal film with metallic property. The impact of the thickness of the dielectric layer placed between the split ring resonators and the Dirac semimetal film on the resonance channel switching is investigated by the electromagnetic simulation. Such active dual channel terahertz switching may have potential applications in advanced terahertz communication.